Diary of a country priest - Bernanos, Georges; Laydu, Claude; Ladmiral, Nicole; Riveyre, Jean; Bresson, Robert; Union Generale Cinematographique (Firm). ([Place of production not identified] Union Generale Cinematographique, 1951)
In Ambricourt, an idealistic young Priest (Claude Laydu) arrives to be the local parish priest. He attempts to live a Christ-like life, but his actions are misunderstood. The community of the small town does not accept him, and although having a serious disease in the stomach, the inexperienced and frail priest tries to help the dwellers, and has a situation with the wealthy family of the location. Written by Claudio Carvalho, Rio de Janeiro, Brazil
Summary taken from: https://www.imdb.com/title/tt0042619/?ref_=fn_al_tt_1
Music by Jean-Jaques Grunenwald; cinematography by Leonce-Henri Burel.
Claude Laydu, Nicole Ladmiral, Jean Riveyre.
DVD
In French.
Keywords: Drama